Behind the Silence: Chinese Voices on Abortion - Nie, Jing-Bao (Rowman & Littlefield Publishers, 2005)
Behind the Silence is the first in-depth work in any language to explore the diverse perspectives of mainland Chinese regarding induced abortion and fetal life in the context of the world's most ambitious and intrusive family planning program. Bringing to light the range of Chinese views and experiences, Nie Jing-Bao draws on extensive primary sources and intensive fieldwork, including surveys by and interviews with hundreds of rural, urban, and overseas Chinese. Nie's exploration of the multi-layered meanings of public silence, official pronouncements, forgotten controversies from the Imperial era, public and private consensus and disagreement, women's personal stories, and doctors' narratives provides compelling evidence on the remarkably varied, sometimes critical, and often tormented voices of the Chinese people. Revealing a surprising range of beliefs and feelings concerning the morality of abortion and fetal life, the book nevertheless finds widespread acceptance of national population policies. It also examines the personal anguish and complex socio-cultural and ethical issues entwined with coerced abortion essential to enforce birth-control policies. In addition, the author argues, the abortion issue illustrates the importance of taking seriously China's internal plurality if Westerners and Chinese are to develop a fruitful cross-cultural dialogue.